The association of hormonal contraceptive use and HPV prevalence - Marks M. (2014)
Women diagnosed with cervical cancer report longer duration and more recent use of combined oral contraceptives (COCs). It is unclear whether COC use is associated with upstream events of human papillomavirus (HPV) infection prior to development of clinical disease. The objective of our study was to assess the association of contraceptive use on the risk for prevalent HPV infection in a cohort of long-term hormonal contraceptive (HC) users. One thousand and seventy (n = 1,070) HIV-negative women aged 20-37 from Thailand enrolled in a prospective study of the natural history of HPV. Baseline HPV genotype information, recency and duration of HC use, sexual behavior, other sexually transmitted infection (STI) information and cervical cytology and histology were assessed. At enrollment, 19.8% and 11.5% of women were infected with any HPV or any high-risk (HR)-HPV, respectively. After adjustment for age, current and past sexual risk behaviors, STI history and cytology, the use of COCs for >6 years was found to be associated with an increased risk of infection with any HPV [prevalence ratio (PR): 1.88 (1.21, 2.90)] and any HR-HPV [PR: 2.68 (1.47, 4.88)] as compared to never users. Recent, long-term COC use was associated with an increased risk for prevalent HPV infection independent of sexual behavior and cervical abnormalities. No similar association was observed for recent or long duration use of progestin-only contraceptives (i.e., depomedroxyprogesterone acetate). These data suggest that COC use may impact early upstream events in the natural history of HPV infection. © 2010 UICC.